HARVARD BUSINESS REVIEW ON STRATEGIES FOR GROWTH (Harvard Business School P. BostonUS, 1998)
Explains compromises and shows how identifying and exploiting them can speed growth and profitability. Looks at how the logic of value innovation helped businesses to sustain high growth revenue and profits. Presents 7 operating principles that govern the acquisition process, and shows how integrating acquisitions can spawn growth. Explores other growth opportunities including diversification, reducing the expenditure on supplementary services, and, creating value in 'market space' by gathering, organizing, selecting, synthesizing, and distributing information.
Located in the Learning Resource Centre